Evaluation of groundwater vulnerability using index-based model approach within parts of Nsukka Sedimentary Basin, Nigeria - Johnson C. Ibuot; Daniel N. Obiora; Emmanuel A. Igwe; Ngozi M. Ugwu (Solid Earth Sciences)
Groundwater vulnerability assessment in Nsukka Sedimentary Basin, Nigeria, is essential for identifying at-risk areas, guiding protective measures, and ensuring sustainable water management due to the region's reliance on groundwater. This study presents an integrated assessment of groundwater vulnerability to pollution utilizing geoelectrical and hydrogeological indices. Vertical Electrical Sounding (VES) surveys were conducted to delineate subsurface lithological variations, while hydrogeological parameters such as porosity, hydraulic conductivity, permeability, and hydraulic resistance were determined to understand groundwater flow dynamics. The VES results revealed four to five geoelectric layers with varying resistivities, thicknesses, and depths, highlighting the complexity of the subsurface. These layers were classified as lateritic sand, medium-coarse brownish sand, coarse sand, and fine-medium coarse-grained sand. The low resistivity observed in parts of the study area suggests the influence of geological structures such as faults and fractures. Groundwater vulnerability indices including Aquifer Vulnerability Index (AVI), GOD index, and GLSI indexes were computed to assess susceptibility to pollution. Porosity, hydraulic conductivity, permeability, and hydraulic resistance were estimated and their values ranged from 27.04 % to 30.21 %, 0.14 m/s to 0.15 m/s, 1.98 to 2.20, and 93.07 to 665.89 respectively. The AVI classified the study area into high and moderate vulnerability classes, with regions of shallow water table exhibiting higher vulnerability. The GOD and GLSI models categorized the study area into low and moderate vulnerability classes. The study offers key insights for enhancing groundwater management in the Nsukka Sedimentary Basin by identifying high-vulnerability zones and recommending protective measures, sustainable land-use, and improved wastewater management.